Clinical trial networks in orthopaedic surgery. Issue 5 (May 2014) - Rangan, A.; Jefferson, L.; Baker, P.; Cook, L.
Abstract : The aim of this study was to review the role of clinical trial networks in orthopaedic surgery. A total of two electronic databases (MEDLINE and EMBASE) were searched from inception to September 2013 with no language restrictions. Articles related to randomised controlled trials (RCTs), research networks and orthopaedic research, were identified and reviewed. The usefulness of trainee-led research collaborations is reported and our knowledge of current clinical trial infrastructure further supplements the review. Searching yielded 818 titles and abstracts, of which 12 were suitable for this review. Results are summarised and presented narratively under the following headings: 1) identifying clinically relevant research questions; 2) education and training; 3) conduct of multicentre RCTs and 4) dissemination and adoption of trial results. This review confirms growing international awareness of the important role research networks play in supporting trials in orthopaedic surgery. Multidisciplinary collaboration and adequate investment in trial infrastructure are crucial for successful delivery of RCTs. Cite this article: Bone Joint Res 2014;3:169–74.